Is it safe to operate on COVID-negative patients during the COVID pandemic? Experience from a tertiary governmental hospital - Jowhara Al-Qahtani (21323033) (2022)
Introduction The novel coronavirus (COVID-19) causes severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which rapidly became a worldwide pandemic. During the pandemic, accurate utilization of medical resources is required while maintaining the safety and well-being of patients and medical staff. This study assessed the safety profile of performing emergency surgical procedures for COVID-19 negative patients confirmed by reverse transcription-polymerase chain reaction (RT-PCR) preoperatively while positive patients were transferred to be managed at a designated COVID-19 hospital. Methods This retrospective descriptive study included COVID-19 negative patients who underwent urologic and general surgery procedures for 3 months from March to May 2020. Demographic characteristics, operative and postoperative hospital course, and postoperative COVID-19 status were evaluated. Results During the 3 months, 865 preoperatively COVID-19 negative patients were evaluated. All patients had uneventful postoperative courses except 2 patients who developed SARS-COV-2 infection postoperatively and were managed conservatively at an isolation facility. The first patient developed bronchospasms and fever upon intubation for laparoscopic appendectomy, with RT-PCR yielding a positive result, while the second developed symptomatic COVID-19 infection 18 days after emergency ureteroscopy. Conclusion Routine screening for COVID-19 using RT-PCR before emergency surgeries provide an acceptable safety profile and cost-effectiveness. COVID-19 negative patients can be managed safely with standard precautions, while positive patients should be managed at designated hospitals. Other Information Published in: IJS Short Reports License: https://creativecommons.org/licenses/by-nc-nd/4.0/ See article on publisher's website: https://dx.doi.org/10.1097/sr9.0000000000000042